Estrategias de marketing relacional de la empresa París Net s.a. De la ciudad de Vinces - Navarro Rodriguez, Jorge Isaias (2022)
The problem originates in the city of Vinces, in the internet services company "Paris Net", a company dedicated to offer internet service via fiber optic and radio link in the city of Vinces and its surrounding areas, which, although it has managed to remain competitive in the local market, it is necessary to propose mechanisms that allow it to grow and become the leading company in internet services in the canton of Vinces, for which it will seek to establish relationship marketing strategies in the company. During the research process conducted in this case study, it was possible to know the problems that may arise in a company if marketing strategies that allow it to grow properly are not applied correctly, in other words, companies must establish mechanisms to consolidate in the market in which they operate, for this it is necessary to apply a study that allows them to know their opportunities, strengths, weaknesses and threats, in order to draw a plan or strategy that will allow the growth proposed at the beginning of its operations. The methodology used will allow to know from direct sources the current situation of the company, but at the same time it will be possible to adapt the current marketing processes, implementing new relationship marketing strategies, allowing the company to adequately reach the population of users and potential customers, which will help it to grow in the market. However, this will only be possible if the relationship marketing activities explained in this case study are planned correctly, which will strengthen the company, consolidating it within the local market.